2014
DOI: 10.7196/samj.8102
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurements in the ankle are not equivalent to blood pressure measurements in the arm

Abstract: Background. Blood pressure (BP) is often measured on the ankle in the emergency department (ED), but this has never been shown to be an acceptable alternative to measurements performed on the arm. Objective. To establish whether the differences between arm and ankle noninvasive BP measurements were clinically relevant (i.e. a difference of ≥10 mmHg). Methods. This was a prospective crosssectional study in an urban ED making use of a convenience sample of 201 patients (18 50 years of age) who were not in need o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…In patients undergoing such surgery, BP monitoring using a pneumatic cuff on the surgical-side arm is avoided to prevent lymphedema [4]. Many studies have evaluated the feasibility of obtaining BP measurements at other sites as a substitute for standard arm BP [3,15,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients undergoing such surgery, BP monitoring using a pneumatic cuff on the surgical-side arm is avoided to prevent lymphedema [4]. Many studies have evaluated the feasibility of obtaining BP measurements at other sites as a substitute for standard arm BP [3,15,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…BP measurements obtained at the lower extremities, including ankle BP, have been well studied [3,5,6,25,26,28,29]. Wilkes et al [6] reported that the ankle is a suitable alternative site for BP measurement only when the arm is not available, because ankle BP measurements tend to be higher than brachial ones [3,6,25,26]. Proposed reasons for the higher leg BP readings include greater resistance of distal vessels, ineffective compression by the cuff on the posterior tibial artery and poor detection of the oscillations [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of NIBP measurement by oscillometry is the determination of MAP from the maximum pulse oscillation during cuff deflation [ 7 ]. Systolic and diastolic pressure can only be estimated indirectly according to some empirically derived algorithm [ 8 ]. Variation in propagation of pressure waves as they pass down the descending aorta results in narrowing and increase in the systolic portions of the pressure wave in the ankle compared with the aortic arch, when measured directly in the anaesthetized dog [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…To control cryptococcal infections, three drugs, namely, fluconazole, amphotericin b and flucytosine, have been recommended for management purposes [ 13 , 14 ]. However, in South Africa, only fluconazole and amphotericin b are routinely used in public health institutions [ 7 , 15 , 16 , 17 ]. To compound this, the clinical application of these two drugs is often limited.…”
Section: Introductionmentioning
confidence: 99%